UPAYA MENINGKATKAN SIKAP APRESIATIF DAN KREATIF DALAM PEMBELAJARAN MUSIK NUSANTARA DENGAN MENGGUNAKAN MEDIA MUSIK KEYBOARD PADA PESERTA DIDIK KELAS VIII A SMP NEGERI 8 PEMALANG - Hariyadi, Sugeng (Universitas Negeri Semarang, 2014)
There are still many students of Pemalang Junior High School 8 who scored below the minimum standard score criteria, that is 75, during the academic year of 2012/2013.This is caused by a number of teachers who have not applied the appropriatemethod or model for learning music, low frequency of students music activity, limited music instrument, and many more. Therefore, collaboratively the author tried to find solutions to conduct action research on problems that arise and resolved them wisely. Together with other teachers,and identification was conducted to find out the most prominent cause of the problem, the methods and models of learning that has not been an efficient and an effective way to increase the studentsâ appreciative and creativeattitude in learning the national music. Based on the background described above, the authors are interested in conducting a research which aims to improve students appreciative and creativeattitude in learning music national music using Keyboard as the media in the eighth grade students of Junior High School 8 Pemalang. This paper aims to answer the issues related to improving music learning method whic is still monotonous and not maximized. In this paper, the method used is based on the action research approach that includes four stages; (1) planning, (2) implementation (3) observation, and (4) analysis and reflection. The data were obtained by collecting data from singingperformance, interviews, documentation of national music learning activities, and observation techniques. The research result shows that the process of learning music using Keyboard as the media can improve studentsâ appreciative and creative attitude. The improvementis also influenced by the activities of learners in the learning process derived from the observations using the observation sheet. The observation result at the end of the cycle indicates that the improvement ranged from 50 to 70%.